CgIPT1 is required for synthesis of cis-zeatin cytokinins and contributes to stress tolerance and virulence in Colletotrichum graminicola - Eisermann, Iris; Motyka, Václav; Kümmel, Stefanie; Dobrev, Petre I; Hübner, Konstantin; Deising, Holger B; Wirsel, Stefan G R (Fungal genetics and biology, 2020)
We have previously shown that the maize pathogen Colletotrichum graminicola is able to synthesise cytokinins (CKs). However, it remained unsettled whether fungal CK production is essential for virulence in this hemibiotrophic fungus. Here, we identified a candidate gene, CgIPT1, that is homologous to MOD5 of Saccharomyces cerevisiae and genes from other fungi and plants, which encode tRNA-isopentenyltransferases (IPTs). We show that the wild type strain mainly synthesises cis-zeatin-type (cisZ) CKs whereas ΔCgipt1 mutants are severely impeded to do so. The spectrum of CKs produced confirms bioinformatical analyses predicting that CgIpt1 is a tRNA-IPT. The virulence of the ΔCgipt1 mutants is moderately reduced. Furthermore, the mutants exhibit increased sensitivities to osmotic stress imposed by sugar alcohols and salts, as well as cell wall stress imposed by Congo red. Amendment of media with CKs did not reverse this phenotype suggesting that fungal-derived CKs do not explain the role of CgIpt1 in mediating abiotic stress tolerance. Moreover, the mutants still cause green islands on senescing maize leaves indicating that the cisZ-type CKs produced by the fungus do not cause this phenotype.
Keywords: Colletotrichum graminicola; Colletotrichum; Saccharomyces cerevisiae Proteins; MOD5; RNA transferová; fylogeneze; virulence; fosfotransferasy s alkoholovou skupinou jako akceptorem; kukuřice setá; Phylogeny; IPT; tRNA-isopentenyltransferase; Cytokinin; Phosphotransferases (Alcohol Group Acceptor); Virulence; Cytokinins; nemoci rostlin; Stress, Physiological; Zea mays; cytokininy; Maize; Zeatin; RNA, Transfer; Saccharomyces cerevisiae - proteiny; Alkyl and Aryl Transferases; Plant Diseases; Abiotic stress; fyziologický stres; zeatin; alkyltransferasy a aryltransferasy